Export Product Quality and Inclusivity in Developing Countries - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2023)
The present study has examined the effect of export product quality improvement on inclusivity in developing countries. Inclusivity is measured by three factors considered simultaneously, namely an increase in the real per capita income, a reduction in within-country income inequality, and poverty reduction. The analysis covers 101 developing countries over the period from 1980 to 2014, and uses primarily the two-step system Generalized Method of Moments estimator. It shows that export product quality improvement results in greater inclusivity, especially in countries that face high levels of economic growth volatility, including large magnitudes of external shocks. Likewise, export product quality improvement leads to a greater inclusivity in countries that experience high levels of export product concentration. The analysis sheds light on the positive contribution of export product quality improvement to inclusivity in developing countries.
Keywords: D63; F14; O11; 330; Export product quality; Inclusivity